Are regional characteristics of tree growth transmitted through the seed - Cunningham, S. W. (My University, 1908)
Introduction: In the fall of 1896 the Division of Forestry, U.S. Dept. of Agr., invited the department of K.S.A.C. to cooperate in a test of forest-tree seed from various localities. It was the object of these experiments to prove or disprove the prevalent idea that a species may grow successfully over a wide area when propagated from seeds taken within restricted limits…
Citation: Cunningham, S. W. Are regional characteristics of tree growth transmitted through the seed. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Seeds; Botany; Forests; Trees; Forestry; Graduating theses; Senior theses; Theses